Effects of Gravity and Inlet Location on a Two-Phase Countercurrent Imbibition in Porous Media - M. F. El-Amin; Amgad Salama; Shuyu Sun (International Journal of Chemical Engineering)
We introduce a numerical investigation of the effect of gravity on the problem of two-phase countercurrent imbibition in porous media. We consider three cases of inlet location, namely, from, side, top, and bottom. A 2D rectangular domain is considered for numerical simulation. The results indicate that gravity has a significant effect depending on open-boundary location.